2015
DOI: 10.1093/trstmh/trv074
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of an isoniazid preventive therapy pilot program among HIV-infected patients in Vietnam, 2008−2010

Abstract: Background WHO recommends screening for TB and evaluation for isoniazid preventive therapy (IPT) based on evidence that they reduce TB-related morbidity and mortality among HIV-infected persons. In Vietnam, an IPT pilot was implemented in two provinces; TB screening, treatment and outcomes were evaluated to inform the adoption and scale-up of IPT. Methods During April 2008 to March 2010, eligible HIV-infected persons aged >15 years, with no previous or current TB treatment, alcohol abuse or liver disease wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In less than 5 years, despite inconsistencies in supply and little history of IPT provision in Myanmar, >80% of MSF's HIV cohort was able to initiate IPT, with >90% able to complete therapy, a rate that is nearly as high as or higher than in most neighbouring countries across South and South-East Asia. 13,14,16,19,20 Myanmar thus compares well across indicators. Only one case of INH resistance was documented among 2740 patients initiating IPT.…”
Section: Public Health Actionmentioning
confidence: 78%
See 1 more Smart Citation
“…In less than 5 years, despite inconsistencies in supply and little history of IPT provision in Myanmar, >80% of MSF's HIV cohort was able to initiate IPT, with >90% able to complete therapy, a rate that is nearly as high as or higher than in most neighbouring countries across South and South-East Asia. 13,14,16,19,20 Myanmar thus compares well across indicators. Only one case of INH resistance was documented among 2740 patients initiating IPT.…”
Section: Public Health Actionmentioning
confidence: 78%
“…13,14 A cohort in Viet Nam, a wealthier country with longer experience with IPT, has shown high completion rates (91.8%), with few cases of loss to follow-up (LTFU) or death. 13,15,16 Médecins Sans Frontières (MSF) has been providing HIV-TB treatment and care in southern Myanmar's Tanintharyi Region since 2004, and was one of the first actors in the country to incorporate IPT into routine HIV care. In Asia, there are some descriptions of IPT in clinical care settings, but there remains a dearth of IPT-related information from Myanmar, and recent IPT policy changes in the country require evidence surrounding the feasibility of IPT integration.…”
mentioning
confidence: 99%
“…evaluated for TPT, and 40 (64%) of these cohorts were seen in HIV clinics. Twenty-one cohorts [17,[66][67][68][69][70][71][72][73][74][75][76][77][78][79] did not use LTBI tests, while 49 cohorts used LTBI tests; 22 used only TST, 12 used only IGRA, and 15 used either IGRA or TST. Among the 56 (80%) studies that reported the type of TPT regimen, mono-isoniazid regimens were the primary regimen prescribed in 50 cohorts (89%), and only one (2%) of the included cohorts primarily prescribed rifamycin-based short regimens (3 to months of rifampicin and isoniazid) [29].…”
Section: Plos Medicinementioning
confidence: 99%
“…Operational studies evaluating TB and HIV programs show the importance of identifying the challenges that underlie the provision of health services to treat both diseases. Proposing strategies for the timely diagnosis of cases as well as for monitoring and effective treatment are imperative [27][28][29][30]. Family Health Strategy coverage is considered a primary resource for improving the health of individuals in cities, as it can improve the access to health services for the population.…”
Section: Discussionmentioning
confidence: 99%